Semantics of the Modal Verb CAN in Scientific Style - Nedobylová, Jana (Univerzita Pardubice, 2017)
The aim of this paper is to map various uses of the modal verb CAN and its meanings in scientific style. The first part of this paper describes the modal verb CAN morphologically, syntactically and semantically. This part primarily explains the individual meanings of CAN, which is reflected in the analysis later in the second part of the paper. The meanings are analyzed based on the contextual factors which determine the particular meaning. The paper also includes a discussion of borderline cases. Conclusion of this paper summarizes the quantitative and qualitative results of the use of the modal verb CAN with regards to the particular functional style.
Sémantika modálního slovesa CAN ve vědeckém stylu
Keywords: modalita; dispoziční; dynamická; jistotní; význam; modální sloveso can; vědecký styl; modality; deontic; dynamic; epistemic; meaning; modal verb can; scientific style